2011
DOI: 10.1002/biot.201100115
|View full text |Cite
|
Sign up to set email alerts
|

Functional finishing of aminated polyester using biopolymer‐based polyelectrolyte microgels

Abstract: This study focuses on a microgel-based functionalization method applicable to polyester textiles for improving their hydrophilicity and/or moisture-management properties, eventually enhancing wear comfort. The method proposed aims at achieving pH-/temperature-controlled wettability of polyester within a physiological pH/temperature range. First, primary amine groups are created on polyester surfaces using ethylenediamine; second, biopolymer-based polyelectrolyte microgels are incorporated using the natural cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…For PET RCM, the second factor seems to play the main role, as the macroporosity remained practically unaffected after functionalization. This latter result of increased WVTR at 65% RH owing to the CM presence on PET RCM is supported by findings of another study which uses microgel CM for functionalization of aminated polyester [36]. …”
Section: Resultssupporting
confidence: 67%
“…For PET RCM, the second factor seems to play the main role, as the macroporosity remained practically unaffected after functionalization. This latter result of increased WVTR at 65% RH owing to the CM presence on PET RCM is supported by findings of another study which uses microgel CM for functionalization of aminated polyester [36]. …”
Section: Resultssupporting
confidence: 67%
“…The intersection of the two asymptotic lines corresponds to the chitosan critical concentration, as shown in Ref. [45]. This concentration was found to be 0.6% (w/v) for the particular chitosan used in this study.…”
Section: Resultssupporting
confidence: 55%
“…One of the key parameters for this outcome was the presence of chitosan in excess. However, it was imperative that this excess was kept to a low limit in order to avoid bulk gel formation or an increase in viscosity when preparing microgel CM from M. The former effect would lead to a continuous coating layer when applied on textile surfaces impairing the textile good properties such as flexibility, crease recovery, and water absorption [45]; the latter effect would influence water diffusion inside the microgel and, therefore, the swelling/shrinking process of the microparticles would be affected [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Once incorporated into textile material surface, it is likely that the SRP microgel particles act as a sensor of temperature and as a valve to regulate the water vapour permeability of the fabric, thus enabling control of moisture content and moisture transmission properties of a modifi ed fabric with small temperature variation in the physiological range. Since moisture permeability is the most important criteria to evaluate textile fabric comfort ability, the water vapour transmission (WVT) values for cotton and PES fabrics coated with poly-NiPAAm/chitosan microgel at low and high relative humidity (R.H.) and temperatures below and above LCST of the microgel have been measured [38][39][40][41]. Th e studies of other research groups with similar microgel system have shown temperature-responsiveness of cotton fabric in terms of higher WVT values at higher temperature [42][43].…”
Section: Stimuli-responsive Polymers (Srps)mentioning
confidence: 99%